High diastereoselective [4 + 2] annulation of β, γ-unsaturated α-keto esters and p-quinone methides: Approach to polysubstituted 4-aryl chromans and tetrahydroquinolines. Issue 31 (30th July 2020) - Si, Wen; Xu, Fan; Liu, Zhanxu; Song, Ran; Lv, Jian
Graphical abstract: Highlights: Synthesis of polysubstituted 4-aryl chromans and tetrahydroquinolines. [4 + 2] Annulation of β, γ -unsaturated α -keto esters with p- quinone methides. DBU as dual nucleophilic agent and shuttled proton transfer. Abstract: DBU-mediated [4 + 2] annulation of β, γ -unsaturated α -keto esters and p -quinone methides has been developed. Under mild conditions, the reaction afforded polysubstituted 4-aryl chromans and tetrahydroquinolines as single diastereoisomer in high yields (up to 91% yield) at room temperature.